Acute urinary retention. (2nd January 2022) - Mavrotas, Jason; Gandhi, Akash; Kalogianni, Vasiliki; Patel, Vikash; Batura, Deepak
Abstract : Acute urinary retention is a common clinical presentation in emergency departments in the UK and is responsible for over 30 000 hospital admissions annually. Awareness of the latest advice and guidelines regarding its presentation, investigation and management is paramount to improve patient outcomes and reduce morbidity. Immediate management of acute urinary retention relies on timely bladder decompression by catheterisation. Knowledge of the routes and types of catheterisation, including the associated risks, complications and contraindications, is essential to allow rapid and early intervention, thus preventing further complications. Differences in the presentation of patients with acute urinary retention reflect varying aetiologies, the knowledge of which determines long-term management and prognosis.